PERTUMBUHAN DAN HASIL BUNGA MATAHARI PADA LAHAN TIDUR DIDAERAH PANTAI KABUPATEN PESISIR SELATAN - O Obel; Firsta Ninda Rosadi; J Jamsari; Ali Rahmat; S Seswita (JURNAL GALUNG TROPIKA, 2022)
Land in the coastal area has not been optimally utilized for agricultural land due to a number of issues, both economically and in terms of cultivation practices. An idea for maximizing the land's potential so that it can be more productive and deliver concrete benefits to the community is required. Sunflower cultivation is one technique to make use of coastal land. The goal of this study was to see how well sunflowers grew and yielded on unused land in coastal areas. The study used a randomized block design, with treatments of three sunflower kinds and two accessions repeated three times. The findings revealed that sunflowers have the potential to be grown on undeveloped land along the coast of the United States.